2023
DOI: 10.21203/rs.3.rs-2559129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosome-transmitted FOSL1 from cancer-associated fibroblasts drives colorectal cancer stemness and chemoresistance through transcriptionally activating ITGB4

Abstract: Background Cancer-associated fibroblasts (CAFs) have been proved to facilitate colorectal cancer (CRC) development, either with boosting chemo-resistance by communicating with CRC cells in the tumor microenvironment. However, the underlying molecular mechanisms remain largely unclear. Methods Relative expressions of FOSL1 and ITGB4, either with their correlations in CRC tissues were assessed using qRT-PCR analysis. Also, Kaplan-Meier survival analysis was employed for evaluating the prognosis. Identification… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Potential strategies could involve targeting their formation, release, or uptake, as well as the bioactive contents they transport, aiming to improve CRC management 92 . Preclinical evidence has shown that agents like GW4869, which suppress exosome release, can diminish the tumor‐promoting actions of CAFs in CRC 89 . Further, blocking the uptake of CAF‐derived exosomes or neutralizing their cargos also showed therapeutic benefits.…”
Section: The Role Of Stromal Cells‐derived Exosomes In Crcmentioning
confidence: 99%
See 3 more Smart Citations
“…Potential strategies could involve targeting their formation, release, or uptake, as well as the bioactive contents they transport, aiming to improve CRC management 92 . Preclinical evidence has shown that agents like GW4869, which suppress exosome release, can diminish the tumor‐promoting actions of CAFs in CRC 89 . Further, blocking the uptake of CAF‐derived exosomes or neutralizing their cargos also showed therapeutic benefits.…”
Section: The Role Of Stromal Cells‐derived Exosomes In Crcmentioning
confidence: 99%
“…CAFs-derived exosomal FOSL1 was validated to enhance the proliferative ability and oxaliplatin resistance of CRC cells. 89 Radiotherapeutic resistance is also a significant challenge in treating CRC, and miR-590-3p plays a crucial role in chemoresistance and radioresistance. Chen et al reported that high expression of miR-590-3p and low expression of CLCA4 were found in CRC tissues and cell lines.…”
Section: Cells -Derived Exosomes In Crcmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon transferring these to CRC cells, they observed a significant increase in stemness, cell proliferation, and resistance to oxaliplatin. FOSL1 facilitates these effects by promoting integrin β4 (ITGB4) transcription [112].…”
Section: The Role Of Fosl1 In Drug Resistancementioning
confidence: 99%